Business Model in Islamic Business Unit: A Lesson from Islamic Boarding Schools in West Java - Adrian Ariatin; Wawan Dhewanto; Oktofa Yudha Sudrajad (Jurnal Internasional Penelitian Bisnis Terapan, 2022)
Traditional Islamic boarding schools or Pesantren in Indonesia are experiencing rapid development. To assist their educational funding, Islamic boarding schools create a business unit in the form of a cooperative called kopontren (hereinafter referred to as Islamic business unit). This study aims to discover what business model should be applied in Islamic boarding schools and what factors lead to the success of Islamic boarding school’s businesses. The case study was carried out by analyzing statistical data on Islamic boarding schools in West Java and conducting in-depth interviews with business actors from six Islamic boarding schools. In addition, the researchers directly observed the schools to determine the business activities and donations that exist. Validation was done by triangulating the data from business actors and academicians who were directly or indirectly involved in the Islamic boarding schools’ businesses. To strengthen the findings, the researchers analyzed the data using qualitative data analysis software called NVivo. The theory of business model, business unit, and Islamic boarding school was used as the basis of this research. This study discovers the efforts made by Islamic boarding schools in meeting their daily operational needs by applying the sharia business model. Through the Islamic business unit, the schools try to take advantage of the existing potential in their environment, participate in training and mentoring programs from the government, and establish cooperation with their networks.